Pengelolaan hutan berkelanjutan: menuju daerah tujuan wisata Kampung Mosso di wilayah perbatasan: Sustainable forest management: towards tiusrism destination Village of Mosso at the border zoness - Mandibodibo, Paulus; Apituley, Frank Leo; Wanaputra, Amadion Andika; Utami, Galuh Putri Windhani; Bukorpioper, Ira Iriani; Ilindamon, Amsal; Rante Tasak, Albida; Arief, Geraldy; Pattiselanno, Freddy (IGKOJEI: Jurnal Pengabdian Masyarakat, 2025)
ABSTRACT  The development plan of Mosso Village as a tourist destination in the border area of Jayapura city needs to involve the local communities (Community Based-Ecotourism). In addition to the potential of hot water, Mosso Village has other Environmental Service Potentials that may contribute to the development of ecotourism areas. Community service activities were carried out from 4 to 7 September 2023 in Mosso village. Identification of the determining factors for the development of tourism areas was carried out using scoring for each variable according to the determining factors based on the opinions of respondents. We found that, community participation was quite good, and the community voluntarily involved themselves in the activity. Mosso village ecotourism has a diverse natural landscape including lowland tropical rainforests, rivers, mountain peaks and hot springs and waterfalls. This has become a major attraction for tourists seeking an authentic nature exploration experience. Variables identified as inhibiting factors need serious attention to be upgraded to moderate status or even become supporting variables for the development of Mosso village as a tourist destination. Infrastructure is indeed very much needed to support the development of the tourist area in Mosso village. The available minimum requirements, such as accommodation and communication facilities, are good. Non-timber forest product species – NTFPs, which exist and have not been optimally utilized, play an important role in supporting the development of Mosso village as a tourist destination. Economically, the development of Mosso village as a tourist destination is quite promising, because it can create jobs for the local population.  Keywords: Border zones Ecotourism; Mosso Vilage; Sustainable Forest Management;   ABSTRAK  Rencana pengembangan Kampung Mosso sebagai daerah tujuan wisata di wilayah perbatasan kota Jayapura perlu melibatkan masyarakat adat setempat (Communty Based- Ecotourism).  Selain potensi air panas, Kampung Mosso memiliki Potensi Jasa Lingkungan lainnya yang diharapkan dapat memberikan kontribusi terhadap pengembangan kawasan ekowisata. Kegiatan pengabdian pada masyarakat dilaksanakan dari tanggal 4 sampai dengan 7 September  2023 di kampung Mosso. Identifikasi terhadap faktor penentu pengembangan kawasan wisata dilakukan dengan menggunakan skoring terhadap setiap variabel sesuai dengan faktor yang menentukan berdasarkan pendapat para responden. Dalam kegiatan pengabdian ini, peran serta masyarakat cukup baik, dan masyarakat yang secara sukarela melibatkan diri dalam kegiatan pengabdian. Ekowisata kampung Mosso memiliki lanskap alam yang beragam termasuk hutan hujan tropis dataran rendah, sungai, puncak gunung serta sumber air panas dan air terjun. Hal ini menjadi menjadi daya tarik utama bagi wisatawan yang mencari pengalaman menjalajahi alam yang otentik. Variabel yang teridentifikasi sebagai faktor penghambat, perlu mendapat perhatian serius untuk ditingkatkan statusnya menjadi moderat atau bahkan menjadi variabel pendukung pengembangan kampung Mosso sebagai daerah tujuan wisata di wilayah perbatasan. Infrastruktur memang sangat dibutuhkan dalam menunjang pengembangan kawasan wisata di kampung Mosso. Persyaratan minimal yang sudah tersedia misalnya penginapan dan sarana komunikasi merupakan hal yang baik. Spesies hasil hutan bukan kayu – HHBK, yang ada dan belum dimanfaatkan secara optimal memainkan peranan penting menunjang pengembangan kampung Mosso sebagai daerah tujuan wisata wilayah perbatasan. Secara ekonomi, pengembangan kampung Mosso sebagai destinasi wisata di wilayah perbatasan cukup menjanjikan, karena mampu menciptakan lapangan pekerjaan bagi penduduk setempat.  Kata kunci: Ekowisata; Kampung Mosso; Pengelolaan hutan berkelanjutan; Wilayah perbatasan